Kepemimpinan Kepala Sekolah Dalam Lembaga Pendidikan di MI Ma’arif NU Karangsari - Dewi Rofikotun Nisa; Salma Indrayanti; Sukataman Sukataman; Imam Nurhakim (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
Education is the quality of a school that requires professional education personnel. Education personnel play an active role in shaping the knowledge and skills of students. Because the education staff will produce higher quality graduates. One way to realize this professionalism requires one of the supports from the principal. The principal is very important in leading those who are directly related to the implementation of educational programs in schools. The approach used in the research at MI Ma'arif NU Karangsari is a qualitative approach, data collection techniques through observation and interviews. The purpose of this paper is to determine the leadership role of school principals in developing institutions and principals' strategies in developing educational institutions. The principal of the MI Ma'arif NU Karangsari school was able to improve the development of existing institutions at the school. This is evident from the curriculum, student affairs, facilities and infrastructure and student learning achievement that goes well and according to teacher performance standards.